Transcription attenuation-derived small RNA rnTrpL regulates tryptophan biosynthesis gene expression in trans. Issue 12 (17th April 2019) - Melior, Hendrik; Li, Siqi; Madhugiri, Ramakanth; Stötzel, Maximilian; Azarderakhsh, Saina; Barth-Weber, Susanne; Baumgardt, Kathrin; Ziebuhr, John; Evguenieva-Hackenberg, Elena
Abstract: Ribosome-mediated transcription attenuation is a basic posttranscriptional regulation mechanism in bacteria. Liberated attenuator RNAs arising in this process are generally considered nonfunctional. In Sinorhizobium meliloti, the tryptophan (Trp) biosynthesis genes are organized into three operons, trpE(G), ppiD-trpDC-moaC-moeA, and trpFBA-accD-folC, of which only the first one, trpE(G), contains a short ORF ( trpL ) in the 5′-UTR and is regulated by transcription attenuation. Under conditions of Trp sufficiency, transcription is terminated between trpL and trpE(G), and a small attenuator RNA, rnTrpL, is produced. Here, we show that rnTrpL base-pairs with trpD and destabilizes the polycistronic trpDC mRNA, indicating rnTrpL-mediated downregulation of the trpDC operon in trans . Although all three trp operons are regulated in response to Trp availability, only in the two operons trpE(G) and trpDC the Trp-mediated regulation is controlled by rnTrpL. Together, our data show that the trp attenuator coordinates trpE(G) and trpDC expression posttranscriptionally by two fundamentally different mechanisms: ribosome-mediated transcription attenuation in cis and base-pairing in trans . Also, we present evidence that rnTrpL-mediated regulation of trpDC genes expression in trans is conserved in Agrobacterium and Bradyrhizobium, suggesting that the small attenuator RNAs may have additional conserved functions in the control of bacterial gene expression.